The psychologist's training permeated by educational inclusion in university education - experience report (Research, Society and Development, 2020)
The present study aims to describe the activities carried out by three psychologists who developed the psychoeducational internship in the Progama de Apoio Psicopedagógico  (PAP) of the Universidade de Fortaleza (UNIFOR) from the perspective of educational psychology, permeated by the proposal of accessibility and respect for differences in University education. This is a report of an internship experience in Educational Psychology and documentary research, referring to the internship advisor's records, reports, and transcripts of attendance in a field diary of the three interns of the Psychology course. The study site, known as PAP, is the sector responsible for promoting accessibility and inclusion of the university, in addition to being an internship field for Psychology students. The trainees in question carried out their activities in different periods (2015-2019), according to the date of admission to the university and the degree, each one, and the internship opportunity offered by the program. Thematic analysis was adopted, defining the thematic nuclei: agent of accessibility and inclusion; psychopedagogical support; psychological support; and facilitators of emotional skills workshops. It was understood that due to the plurality of activities carried out in the internship, there was the development of skills and abilities to deal with, welcome and believe in people with disabilities or specific educational needs. It is concluded that, for the three interns, this experience in the perspective of Educational Psychology offered by PAP, contributed significantly to the modification of looks, concepts, behaviors and new conceptual constructions about differences and respect for them in the context of University education.